A child's introduction to natural history : the story of our living earth-from amazing animals and plants to fascinating fossils and gems - Alexander, Heather, 1967- (New York : Black Dog & Leventhal Publishers, 2016)
"In the tradition of Black Dog's best-selling Child's Introduction books, which include The Story of the Orchestra and A Child's Introduction to the Night Sky, A Child's Introduction to Natural History introduces readers ages 8 to 12 to the fascinating wonders of our natural world. Highlighting every kingdom of life--plants, bacteria, mammals, birds, amphibians, insects, rocks and minerals--the book is also full of charming and witty illustrations by Meredith Hamilton plus 30 photographs throughout. The book delves into topics like geology; prehistoric times, including fossils and dinosaurs; how animals move and fly; evolution; biomes; and more. Sidebars throughout offer biographies of naturalists like Charles Darwin, Mary Anning, and Charles Henry Turner, "--Amazon.com.
What Is Natural History? -- Let's Talk About Earth -- Rocks, Minerals, and Gems -- Try It: Hard Knock Life -- When Did Life First Appear on Earth? -- Once Upon a Time -- Welcome to the Ice Age -- A Lot of Time ... a Lot of Change -- Let's Talk About Plants -- Microlife -- Try It: Grow Mold -- Let's Talk About Animals -- Annelids -- Arthropods -- Mollusks -- Fish -- Oceans and Coral Reefs -- Amphibians -- Freshwater -- Reptiles -- Deserts -- Birds -- Forests -- Mammals -- Grasslands -- Tundra -- Try It: The Blubber Glove -- What's on the Menu? -- Run and Hide: Camouflage and Other Defenses -- I've Got Your Back: Partners and Parasites -- Group Living -- Stay, Go, or Sleep? -- Animal Babies! -- All Gone ... and Going -- All About Natural History Museums -- Index -- Size Comparisons.
Includes index.
Keywords: Natural history -- Juvenile literature; Natural history